Peran Lie Kim Hok (1853-1912) Dalam Membangkitkan Agama Khonghucu Di Indonesia Era 1900-An - Susanto, Dwi (Jurnal Lektur Keagamaan, 2020)
The role of Lie Kim Hok in spreading Confucianism is not only seen from involvement in cultural organizations, but it is seen from the literary works. The research is to discussing the thoughts and contents of Lie Kim Hok's work. This research shown the social practices carried out by Lie Kim Hok in promoting Confucians. This paper uses the concept of structural duality from Anthony Giddens. The results achieved were, Lie Kim Hok gave a response to the social structure of the Chinese peranakan community, especially through the Confucian religious movement. Secondly, Lie Kim Hok's ideas and actions were responded to by the emergence of various religious movements through the writing of religious and educational work by other intellectuals. Third, the social practice was further a response to the colonial discourse so that the movement returned to Confucianism was not only a religious movement, but an attempt at cultural nationalism. This cultural nationalism was further part of the colonial resistance movement. Therefore, Lie Kim Hok is basically resistant to colonial discourse.Key words: Confucius, Chinese descendant, Lie Kim Hok Peran Lie Kim Hok dalam menyebarkan agama Khonghucu tidak hanya terlihat dari keterlibatan dalam organisasi kultural, tetapi hal itu terlihat dari karya yang dihasilkan. Penelitian yang telah dilakukan belum menunjukkan praktik sosial yang dilakukan Lie Kim Hok dalam mempromosikan Khonghucu. Tulisan yang ada membicarakan pemikiran dan isi karya dari Lie Kim Hok. Tulisan ini menggunakan konsep dualitas struktur dari Anthony Giddens. Hasil yang dicapai adalah, pertama, Lie Kim Hok memberikan respon pada struktur sosial di kalangan masyarakat peranakan Cina, khususnya melalui gerakan agama Khonghucu. Kedua, gagasan dan tindakan Lie Kim Hok itu direspon dengan kemunculan berbagai gerakan keagamaan melalui penulisan karya  keagamaan dan pendidikan oleh para intelektual yang lain. Ketiga, praktik sosial tersebut lebih lanjut merupakan sebuah respon atas wacana kolonial sehingga gerakan kembali pada ajaran agama Khonghucu itu bukan hanya sebagai gerakan kegamaan, melainkan sebagai upaya nasionalisme kebudayaan. Nasionalisme kebudayaan ini lebih lanjut adalah bagian dari gerakan resistensi kolonial. Dengan demikian, Lie Kim Hok pada dasarnya bersifat resisten terhadap wacana kolonial.  Kata kunci: Khonghucu, peranakan Tionghoa, Lie Kim Hok